In vitro Lipolysis and Leptin Production of Elephant Seal Blubber Using Precision-Cut Adipose Tissue Slices - Debier, Cathy; Pirard, Laura; Verhaegen, Marie; Rzucidlo, Caroline; Tinant, Gilles; Dewulf, Clément; Larondelle, Yvan; Smith, Donald R.; Rees, Jean-François; Crocker, Daniel E. (Frontiers in Physiology, 2020)
Adipose tissue plays key roles in energy homeostasis. Understanding its metabolism and regulation is essential to predict the impact of environmental changes on wildlife health, especially in fasting-adapted species. However, in vivo experimental work in wild vertebrates can be challenging. We have developed a novel in vitro approach of precision-cut adipose tissue slices from northern elephant seal (Mirounga angustirostris) as a complementary approach to whole animal models. Blubber biopsies were collected from 14 pups during early and late post-weaning fast (Año Nuevo, CA, United States), precision-cut into 1 mm thick slices and maintained in culture at 37°C for at least 63 h. The slices exhibited an efficient response to ß-adrenergic stimulation, even after 2 days of culture, revealing good in vitro tissue function. The response to lipolytic stimulus did not vary between regions of outer and inner blubber, but was higher at early than at late fast for inner blubber slices. At early fast, lipolysis significantly reduced leptin production. At this stage, inner blubber slices were also more efficient at producing leptin than outer blubber slices, especially in the non-lipolytic condition. This model will aid the study of adipose tissue metabolism and its response to environmental stressors in marine mammals.